Rethinking the Traumatic Memory of the Holocaust in Literature (Based on Monika Schneiderman’s Work “Fałszerze pieprzu. Historia rodzinna”) - Yevchuk, Uliana (Respectus Philologicus, 2021)
The article analyzes the attempt to reconstruct the historical memory of the Holocaust in the novel by Polish writer Monika Schneiderman “Fałszerze pieprzu. Historia rodzinna”. The writer questions the issue of Polish-Jewish relations, the responsibility and guilt of Holocaust witnesses to its victims. The author, who has a complex identity, seeks to find out for herself why her Polish family did not show enough sympathy for the suffering of Jews during World War II, including her Jewish relatives. As such indifference on the part of Poles to Holocaust victims was quite common, Monica Schneiderman tries to explain this by examining the relations between societies who lived side by side for centuries in the pre-war period, concluding that the two neighbouring nations lived in separate communities that were not open to each other. Based on the reproduction of the history of her own family, the author seeks answers to difficult questions of universal human values – perception and understanding of others, empathy, compassion. In her works Monica Schneiderman shows the need to include these recently “closed” but extremely important topics in the public discourse.